UPAYA GURU DALAM MENGATASI KESULITAN MEMBACA PADA SISWA KELAS II SDN 261/VI KOTA RAJA - Melda yanti; Tri wera agrita; Refril dani (STKIP Subang, 2025)
His research is motivated by the presence of second-grade elementary school students who still experience difficulties in reading, ranging from not yet recognizing letters, difficulty distinguishing letters that are almost the same in shape and sound, not being able to arrange letters into syllables and words, to reading slowly. This study aims to describe the types of reading difficulties experienced by students, the obstacles faced by teachers, and the teachers' efforts in overcoming reading difficulties.The research method used was qualitative with a qualitative descriptive approach. The research subjects were second-grade teachers. Eight students who had difficulty reading. The research instruments used were observation guides, interview guides, and documentation. Data validity was checked using source and method triangulation techniques. Data analysis used was data reduction, data presentation, drawing conclusions, and verification.The results of the study showed that there were variations in reading difficulties in students, namely two students did not yet recognize letters, three students were not yet able to string letters together, two students were still slow readers. 1) The obstacles experienced by teachers were limited learning time, lack of facilities and infrastructure, differences in students' reading abilities in one class, and lack of parental guidance at home. Likewise, 2) Teachers' efforts included introducing vowels and consonants with letter cards, using picture books, practicing reading texts in stages. The conclusion of the study was that teachers' efforts were quite helpful in overcoming students' reading difficulties, although their implementation was still hampered by internal and external factors.